Analysis of urban health and mobility indicators and their relationship with Covid-19: The Case of Passo Fundo -RS - Camprestrini, Júlia Brum; Müller, Letícia; Silva, Thaísa Leal da (National Journal of City Management, 2024)
Urban areas are expanding rapidly, and the lack of appropriate urban planning has resulted in environmental impacts, compromising the health of cities and their inhabitants. In this context, the concept of Smart Cities, through the use of Information and Communication Technologies (ICTs), can help public managers to outline more assertive strategies for city problems through the measurement of urban indicators. Therefore, the objective of this research is to analyze the health and mobility indicators of Passo Fundo/RS and their relationship with the epidemiological data of COVID-19. The methodology used in this research was a comparison between Passo Fundo’s health and mobility indicators and the same indicators from medium-sized cities in the South of the country best classified in the Connected Smart Cities Ranking of 2021, 2022 and 2023. Soon after, the survey was carried out of the rates of infections and deaths resulting from COVID-19 in these same cities. From the results it was possible to verify that some of the main weaknesses in relation to mobility are public transport and low incentive for active mobility. In the health area, the city presented some satisfactory results, but lacks investment in family health programs and updates to the online medical consultation process. In relation to epidemiological data, it was noticed that the cities best classified in the Ranking had a better fight against the pandemic by implementing ICTs in the consultation management process.